2006
DOI: 10.1186/1476-4598-5-41
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Eag1 potassium channels in clinical tumours

Abstract: Background: Certain types of potassium channels (known as Eag1, KCNH1, Kv10.1) are associated with the production of tumours in patients and in animals. We have now studied the expression pattern of the Eag1 channel in a large range of normal and tumour tissues from different collections utilising molecular biological and immunohistochemical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
194
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(201 citation statements)
references
References 48 publications
7
194
0
Order By: Relevance
“…Selective up-regulation of HERG in several human neoplasms, but not their normal tissue counterparts, has been reported, and pharmacological inhibition of the HERG channel is efficacious in reducing tumor cell proliferation in primary leukemic cells (Pillozzi et al 2002;Jehle et al 2011). Aberrant EAG1 expression has been reported in >75% of human tumors, and its inhibition decreases the proliferation of EAG1-expressing cells (Pardo et al 2005;Hemmerlein et al 2006;Mello de Queiroz et al 2006). While potassium channels have been implicated in cancer, little is known about how ion channels regulate tumor growth and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective up-regulation of HERG in several human neoplasms, but not their normal tissue counterparts, has been reported, and pharmacological inhibition of the HERG channel is efficacious in reducing tumor cell proliferation in primary leukemic cells (Pillozzi et al 2002;Jehle et al 2011). Aberrant EAG1 expression has been reported in >75% of human tumors, and its inhibition decreases the proliferation of EAG1-expressing cells (Pardo et al 2005;Hemmerlein et al 2006;Mello de Queiroz et al 2006). While potassium channels have been implicated in cancer, little is known about how ion channels regulate tumor growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…EAG1 (KCNH1, Kv10.1) has been studied for its potential role in cancer (Pardo et al 1999(Pardo et al , 2005Weber et al 2006). While its normal expression is largely confined to the CNS, EAG1 is highly expressed in >75% of human non-CNS cancers (Hemmerlein et al 2006;Mello de Queiroz et al 2006), although the mechanism by which EAG1 stimulates tumor growth is unknown. It is also unknown whether EAG2 (KCNH5, Kv10.2), which displays much higher expression in the cerebral cortex than the cerebellum (Ludwig et al 2000), has any involvement in cancer.…”
mentioning
confidence: 99%
“…hEag1 has also been correlated to processes like cell-cycle and proliferation, and appears to be implicated in tumour progression in up to 75% of solid tumours. (Bauer and Schwarz 2001;Hemmerlein et al 2006;Pardo 2004). In contrast, hEag2, besides being ubiquitous, does not have the oncogenic potential of hEag1.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, these channels are up-regulated by oestrogens and human papilloma virus (HPV) oncogenes (Díaz et al 2009) and have been reported in almost 50% of patients taking oestrogens (Ortiz et al 2011). Distribution of KCNH1 in normal human tissues is mainly restricted to the brain, myoblasts and adrenal gland and to the reproductionassociated organs placenta and testes (Occhiodoro et al 1998, Pardo et al 1999, Hemmerlein et al 2006, Díaz et al 2009). Nevertheless, the precise role of KCNH1 in normal tissues is nearly unknown.…”
Section: Introductionmentioning
confidence: 99%